2015
DOI: 10.1055/s-0034-1399566
|View full text |Cite
|
Sign up to set email alerts
|

MRI of the Prostate in Germany: Online Survey among Radiologists

Abstract: Purpose: To assess structural, technical, and communicative aspects of dedicated MR examinations of the prostate (MRP) offered by radiologists in Germany. Materials and Methods: We conducted an eight-item online survey among members of the German Radiology Society (DRG). Radiological institutions were asked about their structure, i.?e., either hospital department (HD) or private practice (PP), number of board-certified radiologists, postal regions, number of MRPs in 2011, MR technology and MR sequences applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Paradoxically, the majority of physicians considered the meaningfulness of the prostate MRI as only moderate or poor. One reason for this may be that there is so far no national standard based on which the urologist or treating physician can estimate the reliability of an MRI finding [17]. Studies of experienced centers show high detection rates and negative predictive values with standardized execution and evaluation of the MP-MRI [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Paradoxically, the majority of physicians considered the meaningfulness of the prostate MRI as only moderate or poor. One reason for this may be that there is so far no national standard based on which the urologist or treating physician can estimate the reliability of an MRI finding [17]. Studies of experienced centers show high detection rates and negative predictive values with standardized execution and evaluation of the MP-MRI [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…However, attending physicians must be provided with a deeper understanding of MRI findings in order to make full use of the diagnostic potential of prostate MRI and to make the method overall more cost-effective [18,27]. The 2015 survey of German physicians criticized inadequate feedback from attending physicians to radiologists after prostate MRI [17]. This survey revealed that the majority of respondents were unaware of the PI-RADS classification and that no standardized localization scheme was used to document and explain findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERC application in 3.0-T prostate MRI is one area of ongoing debate [3, 28]. One recent survey among 128 institutions reports that 36 (28%) examined prostates at 3.0 T, but only two (1.5% of all) applied ERCs at 3.0 T [2]. Another survey among 107 institutions found that 5.8% examined prostates with ERC at 3.0 T and 63.5% without ERC at 3.0 T [8].…”
Section: Discussionmentioning
confidence: 99%